PENGARUH CERITA TENTANG ROLE PLAYING SUATU PROFESI TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA - Aristina, Moeljono, Hendy, Aristina, Moeljono, Hendy (S1 Keperawatan, 2012)
Studentsâ learning achievement depends very much on the childâs motivation in their learning activities. Learning motivation can be caused by studentsâ aims or ideals. Nowadays there are many high school students who easily say what their ideals are, but do not know what they can do to reach their ideals. As a connsequence , their motivation is weak and their achievement is pretty low. The aim of the study is to know whether giving the students stories about professional role-play has any influence on studentsâ learning motivation and achievement. This study is an experimental research of the Pre Post Test Control Group Design. The subjects of this study are students of the Social Science Department (IPS) of class II of SMAKSY High School of Surabaya. The sample was obtained through Total Sampling in which two classes are divided into two groups, i.e. the experimental group consisting of 38 students, and the control group which consists of 37 students. The data are collected by using questionnaires, and the results are descriptively analyzed using median scores. This study shows that there is a difference in the median scores of both motivation and learning achievement between the experimental and control groups. The difference in median scores on motivation and learning achievement between the experimental and the control groups after intervention shows that stories about professional role-play has influence on motivation and learning achievement. The result of this study will hopefully be used to elevate studentsâ motivation and learning achievement.Key words: role-playing story, professional, motivation, achievement